Postphlebitic ulcer treatment with platelet-rich plasma and autograft of skin. Case Presentation - Eldis Sánchez Consuegra; Julio Dámaso Fernández Águila; Nancy Soraya Izaguirre Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Cutaneous ulcers not only constitute a serious physical problem, but also a psychological one, as they considerably reduce the patient's quality of life. The case of a 76 - year - old woman with a history of peripheral venous insufficiency and variceal vascular surgery is presented. She was suffering from a large post - phlebitic ulcer (14 x 9 cm) with a long evolution in the right maleolotibial region. It was applied a treatment with autologous plasma gel rich in platelets and then autografting skin free, of medium thickness. After curing the grafted area and performing cures on an outpatient basis for three weeks, healing was achieved in more than 70% of the initially affected area. The case presentation is aimed at showing the benefits of platelet-rich plasma as healing adjuvant.